Examination of current adsorption models for Pb(II) and Cu(II) adsorption onto FeO@MgAl-NO Layered Double Hydroxide in aqueous solution - Ling-Xi Zhao; Ming-Chao Jiang; Ling-Yu Luan; Qing Li; Jing Zhang (Adsorption Science & Technology)
The adsorption of Pb(II) and Cu(II) onto Fe 3 O 4 @Mg 2 Al-NO 3 Layered Double Hydroxide (LDH) as a function of Fe 3 O 4 @Mg 2 Al-NO 3 LDH concentration was studied. An adsorbent concentration effect ( C s effect), namely adsorption isotherm declines as adsorbent concentration ( C s ) increases, was observed. The experimental data were fitted to the adsorption models including the classic Freundlich model, the metastable-equilibrium adsorption theory, the flocculation model, the power function model, and the surface component activity model. The results show that the Freundlich-type metastable-equilibrium adsorption equation, the power function model, and the Freundlich-surface component activity equation can adequately describe the C s effect observed in the batch adsorption tests as all the correlation coefficients ( R 2 ) of the nonlinear plots are higher than 0.96. In other words, their intrinsic parameters simulated from the experimental data are independent of C s value. It is considered that the Freundlich-surface component activity equation is the best model to describe the C s effect of the studied adsorption systems by Akaike Information Criterion evaluation criterion.